Functional Overload Enhances Satellite Cell Properties in Skeletal Muscle - Shin Fujimaki; Masanao Machida; Tamami Wakabayashi; Makoto Asashima; Tohru Takemasa; Tomoko Kuwabara (Hindawi Limited, 2016)
Skeletal muscle represents a plentiful and accessible source of adult stem cells. Skeletal-muscle-derived stem cells, termed satellite cells, play essential roles in postnatal growth, maintenance, repair, and regeneration of skeletal muscle. Although it is well known that the number of satellite cells increases following physical exercise, functional alterations in satellite cells such as proliferative capacity and differentiation efficiency following exercise and their molecular mechanisms remain unclear. Here, we found that functional overload, which is widely used to model resistance exercise, causes skeletal muscle hypertrophy and converts satellite cells from quiescent state to activated state. Our analysis showed that functional overload induces the expression of MyoD in satellite cells and enhances the proliferative capacity and differentiation potential of these cells. The changes in satellite cell properties coincided with the inactivation of Notch signaling and the activation of Wnt signaling and likely involve modulation by transcription factors of the Sox family. These results indicate the effects of resistance exercise on the regulation of satellite cells and provide insight into the molecular mechanism of satellite cell activation following physical exercise.